PsycEXTRA Dataset 2008
DOI: 10.1037/e529812013-001
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Employment and Well-being: Contract Heterogeneity and Differences Among Individuals

Abstract: The increasing use of temporary and part-time employment in recent decades was initially expected to lead to negative effects for the individual. The empirical evidence, however, has been equivocal and the consequences are therefore still unclear. This thesis adopts a psychological approach to alternative employment by investigating how heterogeneity in employment contracts together with individual differences associate with work attitudes and subjective well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 124 publications
(291 reference statements)
0
5
0
1
Order By: Relevance
“…One reason for this mixed evidence may be that non-permanent employees are not a homogeneous group and several factors, including sociodemographics, might modify the association between employment status and mental health (7)(8)(9)(10)(11)(12)(13)(14). A previous study from the same dataset used in this study found consistent socioeconomic inequalities in the onset, duration, and recurrence of work disability (15).…”
mentioning
confidence: 84%
“…One reason for this mixed evidence may be that non-permanent employees are not a homogeneous group and several factors, including sociodemographics, might modify the association between employment status and mental health (7)(8)(9)(10)(11)(12)(13)(14). A previous study from the same dataset used in this study found consistent socioeconomic inequalities in the onset, duration, and recurrence of work disability (15).…”
mentioning
confidence: 84%
“…Darbo produktyvumas didėja, kai darbuotojus paskatina ir palaiko organizacijos vadovai (Weng 2012). Atsižvelgdami į gautąją vadovų paramą, darbuotojai stengiasi dar labiau įsitraukti į organizacijos valdymą, palaikyti esamą įmonės kultūrą (Bernhard-Oettel 2008). Galima teigti, kad šioje teorijoje darbo našumą ir kokybę galima gerinti orientuojantis į vidinį organizacijos klimatą, taip pat į geresnius darbuotojų tarpusavio santykius, atsisakant nustatyti detalias ir konkrečias pareigas.…”
Section: Vadybos Teorijų Vaidmuo Darbo Efektyvumui Laiduotiunclassified
“…One explanation for these inconsistent results is that different types of non-standard workers induce different results. In other words, non-standard workers are not a homogeneous group (Bernhard-Oettel, 2008;Wilkin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, those with a part-time contract could have high job satisfaction because of flexible working hours (Eberhardt and Shani, 1984). Therefore, different types of contract within non-standard employment, or what Bernhard-Oettel (2008) calls heterogeneity among types of contracts, lead to mixed results when measuring job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation